Student or teacher: the tensions faced by a spanish language student teacher - Vélez Rendón, Gloria (Colombian Applied Linguistics Journal, 2003)
The contradictory realities of student teaching viewed through the student teachers’ eyes have been the focus of attention of some recent publications (Britzman, 1991; Knowles & Cole, 1994; Carel, S.; Stuckey, A.; Spalding, A.; Parish, D.; Vidaurri, L; Dahlstrom, K.; & Rand, Ch., 1996; Weber & Mitchell, 1996). Student teachers are “marginally situated in two worlds” they are to educate others while being educated themselves (Britzman, 1991, p. 13). Playing the two roles simultaneously is highly difficult. The contradictions, dilemmas, and tensions inherent in such endeavor make the world of the student teacher increasingly problematic. This is further complicated by the power relationships that often permeate the student teacher cooperating teacher relationship. This paper describes salient aspects of the student teaching journey of Sue, a white twenty-two year old student teacher of Spanish. It uncovers the tensions and dilemmas experienced by the participant in her quest for professional identity. Data collection sources for this study included (a) two open-ended interviews, each lasting approximately forty-five minutes; (b) one school-day long observation; and (c) a copy of the communication journal between the participant and her cooperating teacher. The data revealed that soon upon entering the student teaching field experience, Sue found herself torn by the ambiguous role in which student teachers are positioned: she was neither a full-fledged teacher nor a student. In trying to negotiate a teaching role for herself, Sue was pulled in different directions. She soon became aware of the powerful position of the cooperating teacher and of her vulnerability within the mentoring relationship. The main tension was manifested in Sue’s struggle to develop her own teaching persona on the one hand, and the pressure to conform to her cooperating teachers’ expectations on the other hand. The implications of the study are discussed.